Letramento matemático: desafios para a prática pedagógica de professores de matemática dos anos finais do ensino fundamental - Silva, Karine Camargo e (2024)
This dissertation, developed in the Educational Processes and Language research line of the Postgraduate Program in Education at the University of Passo Fundo/RS, seeks to answer the following question: How do the pedagogical practices of Mathematics teachers in the final years of Education Do they fundamentally enable the development of Mathematical Literacy? The research is based on studies on Mathematical Literacy in the classroom. Authors such as Souza (2017), Fontinele (2020), Soares (2003) and Fonseca (2014) contributed with their theories and studies to understand the topic, as well as to develop effective pedagogical strategies. As a general objective, we sought to analyze the process of adapting new proposals related to the possibilities and difficulties of developing Mathematical Literacy in the pedagogical practices of Mathematics teachers in the final years of Elementary School. For this purpose, qualitative research was carried out using Discursive Textual Analysis. This methodological option, supported by an interpretative analysis of the data, made it possible to The research was based on the concept of Mathematical Literacy proposed by the International Student Assessment Program (PISA, 2012), which considers the ability to use Mathematics to be an essential skill for communicating. to solve problems and make decisions in different contexts of life. Data collection was obtained through semi-structured interviews and teachers' teaching materials. The data were analyzed using Discursive Textual Analysis using the following categories of analysis defined a priori: (1) understanding the role of Mathematics in the modern world; (2) the involvement of Mathematics with social purposes and, (3), the construction of mathematical knowledge based on reasoning and argumentation. In this sense, the results obtained indicated that teachers recognize the importance of Mathematical Literacy, but face challenges in implementing it in their classes. Based on them, the following conclusions were drawn: in category (1), the interviewees perceived Mathematics as an essential tool for understanding and solving everyday problems, as well as for making decisions; in category (2), Mathematics is seen as a social tool that can be used to promote justice, equality and social development; in category (3), Mathematical Literacy is a process of constructing mathematical meanings. The results made it possible to highlight Mathematical Literacy as an important concept for the development of essential mathematical skills with a view to the active participation of students in society. It was also found that promoting Mathematical Literacy requires careful planning and the use of effective strategies to awaken students' curiosity and interest in Mathematics, making it more accessible and meaningful to their lives.